PERSEPSI KELUARGA PENERIMA BERAS MISKIN (RASKIN) DI KENAGARIAN PANTI KECAMATAN PANTI KABUPATEN PASAMAN - -, Yulia - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain information on the Perception of Poor Families Recipients Rice (Raskin) in Kenagarian Panti Panti Subdistrict Pasaman. Include: Quality Raskin received by the recipient family Raskin Raskin and Time Recipient to recipient families Raskin. type of research is qualitative. Informants in this study consisted of families receiving Raskin, head of the ellipse and village trustee. Technique is the determination of informants by the Snowball Sampling researchers. Where the subject is taken based informants who know the issues to be investigated. Data was collected through observation, interviews, and documentation. The results of the research in the field as follows: Quality Raskin in Kenagarian Panti still not good, because according to the results of interviews conducted in the field to the recipient families in Kenagarian Panti Raskin said that they receive quality Raskin Baras often gets less good. Raskin so the quality is not in accordance with the wishes and expectations of them as seen from the quality of the rice. Time division should Raskin every month. but the fact the field Raskin recipient families in Kenagarian Panti still maximal application of the time-sharing Raskin. Raskin recipient families receive once every two months. so that time is not in accordance with the distribution of Raskin advocated by the government and hope the recipient family wishes Raskin.